The effects of starter culture addition on chemical, microbiologic and sensory quality characteristics of ivriz checse - Nevzat Demir; Mustafa Nizamiıoğlu (Eurasian Journal of Veterinary Sciences)
In this study, addition of starter culture in traditional Ivriz cheese production and the effects of its on chemical, microbiological and sensory quality characteristics of the cheese during ripening period. Two groups of cheese were produced. Samples of group A cultured and samples of B were traditionally produced. On the other hand, the market cheese is obtained from Institute of Ereğli Sheep Production Station and performed group C. The chemical and microbiological analyses have been done in 1„ 15., 30., 60., 90. and 120lh days ol ripening and the sensory analyses has been done in 60.. 90. and 120th days of ripening. The samples belong to group A showed lower humidity and salt contents in dry matter at the beginning of ripening but later stages similar results have been obtained to the other groups. Fat levels in dry matter ol group A, samples were higher in initial stage but during the ripening period they hava show similar results to the others. Acidity value of A group Ivriz cheese sampies were higher than group B and C groups during the ripening period. Generally, it has been observed that A group of cheese has low level pH. Higher protein levels found in C group Ivriz cheese compare to A and B levels. There are no significant differences between groups for generally microorganisms, staphylococcus, mould and yeast lor experimental Ivriz cheese products. Cheese produced culture addition has the highest total points average in the 120,ri day of the ripening period. In conclusion; it was observed that using of the cullure in the Ivriz cheese production increased the quality ol cheese and decreased levels of ripening period in Ivriz cheese. Market cheese has to ripen in 90 days and sell. Ivriz cheese produced with culture addition showed similar sensory analyses results in the 60,h day of ripening period to the market cheese. It is concluded thai culture adding cheese production decrease to ripening period; therefore storage is short and microbiologic quality also best compare to other groups.